Prospectives for Gene Therapy of Retinal Degenerations - Thumann, Gabriele (Bentham Science Publishers, 2012)
Retinal degenerations encompass a large number of diseases in which the retina and associated retinal pigment epithelial (RPE) cells progressively degenerate leading to severe visual disorders or blindness. Retinal degenerations can be divided into two groups, a group in which the defect has been linked to a specific gene and a second group that has a complex etiology that includes environmental and genetic influences. The first group encompasses a number of relatively rare diseases with the most prevalent being Retinitis pigmentosa that affects approximately 1 million individuals worldwide. Attempts have been made to correct the defective gene by transfecting the appropriate cells with the wild-type gene and while these attempts have been successful in animal models, human gene therapy for these inherited retinal degenerations has only begun recently and the results are promising. To the second group belong glaucoma, age-related macular degeneration (AMD) and diabetic retinopathy (DR). These retinal degenerations have a genetic component since they occur more often in families with affected probands but they are also linked to environmental factors, specifically elevated intraocular pressure, age and high blood sugar levels respectively. The economic and medical impact of these three diseases can be assessed by the number of individuals affected; AMD affects over 30 million, DR over 40 million and glaucoma over 65 million individuals worldwide. The basic defect in these diseases appears to be the relative lack of a neurogenic environment; the neovascularization that often accompanies these diseases has suggested that a decrease in pigment epithelium-derived factor (PEDF), at least in part, may be responsible for the neurodegeneration since PEDF is not only an effective neurogenic and neuroprotective agent but also a potent inhibitor of neovascularization. In the last few years inhibitors of vascularization, especially antibodies against vascular endothelial cell growth factors (VEGF), have been used to prevent the neovascularization that accompanies AMD and DR resulting in the amelioration of vision in a significant number of patients. In animal models it has been shown that transfection of RPE cells with the gene for PEDF and other growth factors can prevent or slow degeneration. A limited number of studies in humans have also shown that transfection of RPE cells in vivo with the gene for PEDF is effective in preventing degeneration and restore vision. Most of these studies have used virally mediated gene delivery with all its accompanying side effects and have not been widely used. New techniques using non-viral protocols that allow efficient delivery and permanent integration of the transgene into the host cell genome offer novel opportunities for effective treatment of retinal degenerations.